(untitled) (Experimental biology, 2015)
Cell growth and lipid accumulation in cells of isolated strains of microalgae were studied when these microalgae:Parachlorella kessleri DZP-5, Chlorella vulgaris K6 and Parachlorella kessleri Uz-1 cultured in various conditions. The growth of the studied microalgal strains was measured by spectrophotometry. The optimal conditions for growth was observed in the mixotrophic conditions. To induce the lipids synthesis in the isolated microalgal strains, it was preferable to culture in growth medium in which the concentration of nitrogen was less by 10 times compared with the standard.Accumulation of lipids in the cells of the isolates was assessed by fluorescence spectroscopy using fluorescent dyes, Neil Red. The highest accumulation of lipids was observed in cells of Parachlorella kessleri DZP-5 strains recorded in the growth condition which called “nitrogen starvation” condition.